Identifying and Minimising Uncertainty for Experimental Journal Bearing Studies - G. D. Wale; D. Mba (International Journal of Rotating Machinery)
Over the last few decades, different experimental methods, with varying forms of data analysis, have been employed on a wide range of journal bearing types. Under these circumstances, it is not surprising that the results presented, and their accuracy, are subject to varying scatter. Many of the assessments have been rather imprecise, often using unquantified statements such as “generally good agreement with predictions.” Most authors seem to have accepted that the appreciable scatter of results, especially in the dynamic oil film coefficients, was inevitable. Uncertainty is defined as the estimate of the errors. Note that the estimate may often be too optimistic because some sources of error have not been identified. This paper highlights sources of error for experimental journal studies, including some associated with the measurement system and physical misalignment. It is intended that this paper presents a coherent source of information on best practice in the field of experimental bearing research, offering a clearly prescribed methodology to estimate uncertainty and reduce error. The results of calculations of the sensitivity of the dynamic bearing coefficients to experimental errors in some commonly used rig configurations are presented. It is shown that one of the excitation schemes gives significantly lower sensitivity, but even this scheme has quite high sensitivity to measurement errors, especially phase. In conclusion, some of the critical precautions in the search for good quality results for experimental journal bearing studies are described.